Effects of lithium isotopes on sodium/lithium co-transport and calcium efflux through the sodium/calcium/lithium exchanger in mitochondria - Bukhteeva, Irina; Rahman, Fasih A.; Kendall, Brian; Duncan, Robin E.; Quadrilatero, Joe; Pavlov, Evgeny V.; Gingras, Michel J. P.; Leonenko, Zoya (Frontiers in Physiology, 2024)
The effects of lithium (Li) isotopes and their impact on biological processes have recently gained increased attention due to the significance of Li as a pharmacological agent and the potential that Li isotopic effects in neuroscience contexts may constitute a new example of quantum effects in biology. Previous studies have shown that the two Li isotopes, which differ in mass and nuclear spin, have unusual different effects in vivo and in vitro and, although some molecular targets for Li isotope fractionation have been proposed, it is not known whether those result in observable downstream neurophysiological effects. In this work we studied fluxes of Li+, sodium (Na+) and calcium (Ca2+) ions in the mitochondrial sodium/calcium/lithium exchanger (NCLX), the only transporter known with recognized specificity for Li+. We studied the effect of Li+ isotopes on Ca2+ efflux from heart mitochondria in comparison to natural Li+ and Na+ using Ca2+-induced fluorescence and investigated a possible Li isotope fractionation in mitochondria using inductively coupled plasma mass spectrometry (ICP-MS). Our fluorescence data indicate that Ca2+ efflux increases with higher concentrations of either Li+ or Na+. We found that the simultaneous presence of Li+ and Na+ increases Ca2+ efflux compared to Ca2+ efflux caused by the same concentration of Li+ alone. However, no differentiation in the Ca2+ efflux between the two Li+ isotopes was observed, either for Li+ alone or in mixtures of Li+ and Na+. Our ICP-MS data demonstrate that there is selectivity between Na+ and Li+ (greater Na+ than Li+ uptake) and, most interestingly, between the Li+ isotopes (greater 6Li+ than 7Li+ uptake) by the inner mitochondrial membrane. In summary, we observed no Li+ isotope differentiation for Ca2+ efflux in mitochondria via NCLX but found a Li+ isotope fractionation during Li+ uptake by mitochondria with NCLX active or blocked. Our results suggest that the transport of Li+ via NCLX is not the main pathway for Li+ isotope fractionation and that this differentiation does not affect Ca2+ efflux in mitochondria. Therefore, explaining the puzzling effects of Li+ isotopes observed in other contexts will require further investigation to identify the molecular targets for Li+ isotope differentiation.